The relationship of job burnout to organizational commitment and moral distress in nurses - Mehran Naghibeiranvand; Anahita Abbasinargheseh; Zohreh Jafari; Maryam Babaei Khomeini; Moein Alishahi (Shahrekord University of Medical Sciences, 2022)
Background and aims: Nursing is a stressful profession that leads to job burnout in the long term. In addition to nurses and patients, organizations pay for consequences of job burnout, as well. Moral distress is also a source of potential harm to nurses. The present study was conducted to investigate the relationship of job burnout to organizational commitment and moral distress in nurses. Methods: This descriptive, correlational study was performed on 100 nurses in Shahid Rahimi Hospital of Khorramabad who were enrolled by convenience sampling method. Data collection tools were the Maslach Burnout Inventory, Kevin-Dick and Beverly Organizational Commitment Scale, and Corley's Moral Distress Scale. Data analysis was performed by SPSS 23 using descriptive statistics, independent t test and ANOVA. Significance level (P) was considered to be<0.05. Results: Around 84% of the participants were female and 92% worked on a rotating shift schedule. The mean±standard deviation (SD) scores of job burnout, organizational commitment and moral distress were 78.93±24.13, 47.00±12.28 and 38.84±12.74, respectively. Also there was a statistically significant, inverse correlation between job burnout and organizational commitment (P=0.003), while there was no statistically significant relationship between job burnout and moral distress (P=0.301). Conclusion: Identifying and eliminating the causes of job burnout can contribute to improving organizational commitment in nurses.